The Implications of Matthew 15: 21-28 to Christian Teacher Multicultural Problems - Esther Yunita Dewi (Sekolah Tinggi Teologi Baptis, Jakarta, 2019)
The reality of the plurality of the Indonesian nation is the reason for the occurrence of multicultural problems in society, including in the educational environment, both occurring for teachers and students. The method used in this research is descriptive analysis method, research that tries to describe by interpreting the consequences that are happening. While the type of research used is qualitative by conducting literature studies, a study of biblical texts in Matthew 15: 21-28, and field studies. The results of the study are: first, the teacher needed to increase knowledge about multicultural and multicultural education. Second, developing creative attitudes in learning. Third, have an open attitude. Fourth, have an attitude of exemplary, and fifth have the attitude of seeing other people who are different from themselves as images of God.